Cannabidiol‐Loaded Poly Lactic‐Co‐Glycolic Acid Nanoparticles with Improved Bioavailability as a Potential for Osteoarthritis Therapeutic. (3rd April 2023) - Jin, Zhiqiang; Zhan, Yanting; Zheng, Li; Wei, Qingjun; Xu, Sheng; Qin, Zainen
Abstract: Cannabidiol (CBD) is a non‐intoxicating cannabinoid from cannabis sativa that has demonstrated efficacious against inflammation, which can be considered as a potential drug for arthritis treatment. However, the poor solubility and low bioavailability limit its clinical application. Here, we report an effective strategy to fabricate Cannabidiol‐loaded poly(lactic‐co‐glycolic acid) copolymer (CBD‐PLGA) nanoparticles (NPs), with a spherical morphology and an average diameter of 238 nm. CBD was sustained release from CBD‐PLGA‐NPs, which improved the bioavailability of CBD. The CBD‐PLGA‐NPs effectively protect the damage of LPS to cell viability. We observed that CBD‐PLGA‐NPs significantly suppressed LPS‐induced primary rat chondrocyte expression of inflammatory cytokines, including interleukin 1β (IL‐1β), interleukin 6 (IL‐6), tumor necrosis factor‐α (TNF‐α) and matrix metalloproteinase 13 (MMP‐13). Remarkably, CBD‐PLGA‐NPs also showed better therapeutic effects of inhibiting the degradation of the extracellular matrix of chondrocytes than equivalent CBD solution. In general, the fabrication CBD‐PLGA‐NPs showed good protection of primary chondrocytes in vitro and is a promising system for osteoarthritis treatment. Abstract : Cannabidiol (CBD) have been considered as a potential drug for arthritis treatment . In this article, we describe an effective strategy to fabricate CBD‐loaded poly lactic‐co‐glycolic acid nanoparticles (CBD‐PLGA‐NPs), with inhibiting the expression of inflammatory factors, increasing cellularity, and improving structural changes, which can be regarded as a potential system to treat OA.